Associations of alcohol consumption with blood pressure, lipoproteins, and subclinical inflammation among Turks - Onat, Altan; Hergenc, Guelay; Dursunoglu, Dursun; Ordu, Serkan; Can, Guenay; Bulur, Serkan; Yuksel, Husniye (ELSEVIER SCIENCE INC, 2008)
Gender-related impact of alcohol consumption on blood pressure (BP), serum lipoprotein profile, and C-reactive protein (CRP) concentrations was evaluated prospectively. Alcohol drinking status was assessed as abstainers and categories of light, moderate, and heavy (daily >40 ml ethanol) intake. Mean age of the 3,443 men and women who were followed up for a mean of 7.4 years was 47.6 +/- 12 years. In each multivariable linear or logistic regression analysis, alcohol drinking status was adjusted for age, sex, smoking status, and physical activity. Among men. drinking was significantly associated positively with low-density lipo protein (LDL) cholesterol, apolipoprotein (apo) B, systolic and diastolic BR and with CRP in a log-linear manner exhibiting features of a threshold at heavy drinking. With respect to response of serum triglycerides to light-to-moderate drinking, whereas men exhibited a significant increase, women exhibited a decline (P < .05). Lower BPs (P < .03) and CRP levels (P = .032) were observed in female drinkers than abstainers and, as distinct from men, no increases in LDL cholesterol and apoB were noted. Heavy drinking tended to protect the sexes against the risk of developing low high-density lipoprotein cholesterol levels in prospective multi adjusted analyses. Sex modulates response of cardiometabolic risk variables to moderate alcohol consumption among Turks. Only women respond with lower triglycerides and CRP, whereas men show a log-linear positive association of drinking categories with BP, LDL cholesterol, apoB, and CRP. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Alcohol consumption; Apolipoprotein B; Blood pressure; C-reactive protein; LDL cholesterol; Metabolic syndrome; CORONARY-HEART-DISEASE; HIGH-DENSITY-LIPOPROTEIN; RISK-FACTORS; LIPID LEVELS; METAANALYSIS; CHOLESTEROL; MEN; MARKERS; HYPERTENSION; MORTALITY; Substance Abuse; Pharmacology & Pharmacy; Toxicology